PELAKSANAAN PEMBERIAN UPAH MINIMUM TERHADAP TENAGA PENDIDIK YAYASAN TK TUNAS HARAPAN PEKANBARU - Pebi Ikasari Tarigan; Hayatul Ismi; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
The wage means that the work reward or achievement that must be paid by the employer for the work is required to fulfill the achievement of doing the work under someone else's order. One of the foundations in the field of education, the TK Tunas Harapan Pekanbaru Foundation, is one of the foundations in the city of Pekanbaru that still provides wages that are not in accordance with the rules and views on labor welfare that have been regulated by the government. The formulation of the problem in this research is How is the implementation of wages to educators at the TK Tunas Harapan Pekanbaru Foundation, What are the factors that cause wages under UMK at the TK Tunas Harapan Pekanbaru Foundation.This type of research is a study of Sociological Law. The nature of this research is to use empirical research based on primary data. This research was conducted at the TK Tunas Harapan Pekanbaru Foundation on Jl. Melayu No. 52, Pekanbaru City. Conclusions in this study. First, Educators should have written employment agreements. Second Educators should have the right to agree on Regency / City working hours (UMK). That way there is a balance between the rights and obligations received and that must be done by educators. Author's suggestion there should be an agreement on the regulation of working hours and equal pay between educators and foundation managers.Keywords: Work-Time-Wage-Work Agreement